Lysine-Specific Demethylase 1A as a Promising Target in Acute Myeloid Leukemia - Magliulo, Daniela; Bernardi, Rosa; Messina, Samantha (Frontiers in Oncology, 2018)
Acute myeloid leukemia (AML) is a heterogeneous hematopoietic malignancy characterized by the accumulation of incompletely differentiated progenitor cells (blasts) in the bone marrow and blood, and by suppression of normal hematopoiesis. It has recently become apparent that the AML genome is characterized by recurrent mutations and dysregulations in epigenetic regulators. These mutations frequently occur before the onset of full blown leukemia, at the pre-leukemic phase, and persist in residual disease that remains after therapeutic intervention, thus suggesting that targeting the AML epigenome may help to eradicate minimal residual disease and prevent relapse. Within the AML epigenome, lysine-specific demethylase 1 A (LSD1) is a histone demethylase that is found frequently overexpressed, albeit not mutated, in AML. LSD1 is a required constituent of critical transcription repressor complexes like CoREST and nucleosome remodeling and deacetylase (NuRD), and abrogation of LSD1 expression results in impaired self-renewal and proliferation, and increased differentiation and apoptosis in AML models and primary cells, particularly in AMLs with MLL- and AML1-rearrangements, or erythroid and megakaryoblastic differentiation block. On this basis, a number of LSD1 inhibitors have been developed in the past decade, and few of them are currently being tested in clinical trials for patients with AML, along with other malignancies. To date, the most promising application of this therapeutic strategy appears to be combination therapy of LSD1 inhibitors with all-trans retinoic acid (ATRA) to reactivate myeloid differentiation in cells that are not spontaneously susceptible to ATRA treatment. In this review, we provide an overview of LSD1 function in normal hematopoiesis and leukemia, and of the current clinical application of LSD1 inhibitors for the treatment of patients with AML.